Factors associated with removal of postpartum intrauterine contraceptive device among acceptors in rural areas of Nadia district, West Bengal: a case-control study - Pal, Jayita; Sharma, Jitu; Satapathy, Sankalpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The unmet need for contraception remains high in the postpartum period. Postpartum intrauterine contraceptive device (PPIUCD), despite being an effective and well-suited contraceptive method for this period, many women discontinue its use due to various reasons just after a few days or weeks. The study aimed to identify the factors associated with the removal of the same. Methods: A community-based case-control study had been conducted in Nadia district of West Bengal. A multi-stage sampling technique had been applied to identify and interview the cases and controls with the help of a predesigned pretested semi-structured schedule. Results: The overall removal and expulsion rates were found to be quite high (21.5% and 16.3% respectively). Multivariate analysis revealed that acceptors belonging to joint family, educated only up to middle level, if place of delivery and insertion of PPIUCD was BPHC, the same had been inserted by nursing staff, experienced pain after insertion, not given consent before insertion, not counselled ever on PPIUCD, not decided to accept PPIUCD before delivery, not satisfied with its use and undergone no follow up visit after its insertion, were having higher odds of removal of the same. Conclusions: Rigorous counselling during the antenatal period should be focused to achieve a declining trend regarding PPIUCD removal.